Effect of different periods of hyperbaric oxygen on ischemia-reperfusion injury of rat small bowel Efeitos de diferentes períodos de oxigenação hiperbárica na lesão de isquemia e reperfusão de intestino delgado de ratos - Paulo Roberto Bertoletto (Acta Cirurgica Brasileira, 2008)
PURPOSE: To determine whether hyperbaric oxygen (HBO) could effectively protect the small intestine mucosa against an ischemic insult, according to different periods of application. METHODS: The gut of 32 male rats was subjected to 60-min ischemia (clamping the mesenteric artery and vein); After they were further reperfused upon clamp opening during 60 min. Animal groups were as follows. GII = placed on HBO during the ischemia period; GIII = placed on HBO during reperfusion; GIV = treated with HBO throughout the ischemia-reperfusion period. Some animals (GI) did not receive HBO treatment at all and served as reference of ischemia-reperfusion injury (IR). HBO was carried out in a cylindrical acrylic chamber (2.0 ATA). Samples of small bowel were prepared for H.E staining for histological evaluations. RESULTS: The histological injury of mucosa was significantly less when HBO was administered during the ischemia period (17.6 ± 0.6) as compared with the IR (21.3 ± 1.8). HBO was not effective when applied during reperfusion (23.1 ± 2.1) or during the ischemia plus reperfusion period (18.7 ± 1.9). The thickness of the mucosa was preserved by HBO in ischemia (327.50 ± 30.23 µm) in comparison with the IR (172.79 ± 5.95 µm). In the periods of reperfusion (162.50 ± 6.05 µm) and ischemia plus reperfusion (296.49 ± 20.01 µm) the mucosa revealed a structural injury. CONCLUSION: Hyperbaric oxygen affects the ischemic insult of small bowel, being the favorable effect obtained when hyperbaric oxygen was administered early in the ischemic period. OBJETIVO: Determinar se a oxigenação hiperbárica (OHB) protege a mucosa do intestino delgado de ratos após isquemia e reperfusão. MÉTODOS: 32 ratos machos foram submetidos a clampeamento da artéria e da veia mesentéricas superiores durante 60 minutos (isquemia) seguido de 60 minutos de reperfusão. Após estes procedimentos os animais fora separados em quatro grupos, a saber: grupo I (GI) isquemia e reperfusão (IR); grupo II (GII) submetido a OHB concomitante a isquemia, Grupo III (GIII) submetido a OHB durante a reperfusão e, grupo IV (GIV) submetido a OHB durante o período de isquemia e de reperfusão. A OHB foi realizada em câmara acrílica (2.0 ATA). Após anestesia, fragmentos do intestino delgado (íleo) foram fixados e processados para inclusão em parafina sendo os cortes corados pelo HE. As lâminas foram avaliadas quanto a presença de lesões histopatológicas da mucosa e avaliado a espessura da mucosa. RESULTADOS: A lesão histopatológica da mucosa foi significativamente inferior quando a OHB foi administrada na isquemia (12.6 ± 0.6) em comparação com o IR (21.3 ± 1.8). A OHB não foi efetiva quando aplicada durante a reperfusão (23.1 ± 2.1), ou durante a isquemia e reperfusão (18.7 ± 1.9). A espessura da mucosa foi preservada pela OHB na isquemia (327,50 ± 30.23 µm) em comparação com o IR (172.79 ± 5.95 µm). Nos períodos de reperfusão (162.50 ± 6.05 µm) e a isquemia (296.49 ± 20.01 µm) a mucosa apresentou lesão estrutural. CONCLUSÃO: A oxigenação hiperbárica protege a mucosa intestinal quando realizada durante o período de isquemia.